Role of Colloidal Drug Delivery Carriers in Taxane-mediated Chemotherapy: A Review - Kumar, Pramod; Raza, Kaisar; Kaushik, Lokesh; Malik, Ruchi; Arora, Shweta; Prakash Katare, Om (Current Pharmaceutical Design, 2016)
Chemotherapy is one of the most frequently employed and reliable treatment options for the management of a variety of cancers. Taxanes (paclitaxel, docetaxel and cabazitaxel) are frequently prescribed to treat breast cancer, hormone refractory prostate cancer, non-small cell lung cancer and ovarian cancer. Most of the commercial products of taxanes are available as injectables, which are not patient compliant and are associated with frequent side effects like ototoxicity, baldness and neurotoxicity. Most of these concerns are ascribable to the presence of toxic solvents in these commercial formulations, which are used to solubilize these drug(s). However, there have been several attempts to develop toxic solvent free taxane formulations, especially employing novel drug delivery systems (NDDS). These systems have been reported to result in the advancement of anticancer activity, therapeutic index, stability, biocompatibility, tissue or organ targeting, encapsulation capacity, tissue permeability, oral bioavailability, reduced toxicity and reduced incidences of abnormal reactions, sustained and controlled release in comparison to the conventional solvent-based formulations. The review is an attempt to analyze the potential of NDDS-mediated taxane delivery for safer and effective cancer chemotherapy.
Keywords: Paclitaxel